PENERAPAN METODE PENCEGAHAN LUKA DECUBITUS PADA PASIEN BEDREST TOTAL MELALUI PERAWATAN KULIT DENGAN NIGELLA SATIVA OIL DI RSUD K.R.M.T. WONGSONEGORO KOTA SEMARANG - Ainnur Rahmanti; Ajeng Kartika Ningrum (Jurnal Kesehatan Medika Udayana, 2019)
Pressure ulcer is local injury of skin of subtexture it, generally at bump of bone, the effect of pressure or pressure combination with friction or seraping. To preventing the risk of pressure ulcer at total bedrest patient need to treatmen of skin by Nigella Sativa Oil. The purpose of this case study is to be analyze of application by prevention of pressure ulcer pressure sores method at total bedrest patient. The type of this research is descriptive with method of the case study. The subject of this research use two patient who is sustain of total bedrest more than 3 eith enteria for assesment result by Norton 14 scale less than 14 which it is categorized risk of everage pressure ulcer. The result of this research can be conclude at subject I from 10 Norton scale to 13 scale, at subject II from 13 Norton scale to 16 scale. So, at the time from it review with high severe of injury to use the Design from every the category that obtains the result 0 which it means not happens pressure ulcer injury by both of subject. The nurse must be applies by Nigella Sativa Oil therapy at total bedrest patient to can prevent of pressure ulcer risk.